Oxidizing decarbonization characteristics of MgO–C refractories for electric arc furnace steelmaking with CO2 utilization. Issue 24 (15th December 2022) - Tian, Bohan; Zhou, Yun; Wei, Guangsheng; Zhu, Rong; Wu, Wenhe; Yang, Lingzhi
Abstract: Bottom-blowing is an effective metallurgical method in elecric arc furnace (EAF) steelmaking, which uses scrap as the primary raw material with lower carbon emissions. With the proposal and application of the novel bottom-blowing method with CO2 and Ar mixed injection in EAF steelmaking, it is necessary to improve the service life of bottom-blowing elements and realize the steelmaking reactors' furnace life. In this study, oxidation experiments were carried out on cylindrical MgO–C refractories in a CO2 -Ar environment with different CO2 ratios, and the oxidation kinetics mechanism, phase composition, and the effect of different CO2 ratios on pore distribution and microstructure were investigated. The effective diffusion coefficient decreased from 1.51 × 10 −5 m 2 /s to 0.75 × 10 −5 m 2 /s when CO2 ratio decreased from 100% to 20%; the pore size was mainly distributed at approximately 4.69 μm, and the porosity was 13.74%. The same phenomenon was observed in the microstructure; the oxidation products formed by Al antioxidants existed in both decarburized and unoxidized regions, forming pore blocks that inhibited the diffusion of gaseous reactants and gaseous products.